2021
DOI: 10.3390/medicina57050489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emotional Dysregulation Features in Cyclothymia and Adult ADHD

Abstract: Background and Objectives: Emotional dysregulation is central to the problem of the overlap between attention-deficit/hyperactivity disorder (ADHD) and cyclothymia. The aim of the study was to evaluate comorbidity rates between ADHD and cyclothymic disorder and to explore demographic and clinical differences among the groups, focusing on affective temperament and emotional dysregulation. Materials and Methods: One hundred sixty-five outpatients attending the Second Psychiatry Unit at the Santa Chiara Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…When the criteria were not clear, the inclusion or exclusion of the article was decided among all three authors. S1 Table shows the bibliometric properties of the included articles [13,[51][52][53][54][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], which are marked with � in the references section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the criteria were not clear, the inclusion or exclusion of the article was decided among all three authors. S1 Table shows the bibliometric properties of the included articles [13,[51][52][53][54][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], which are marked with � in the references section.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, Ru ¨fenacht et al [63] found that the ADHD group had higher emotion dysregulation scores compared to other clinical and community samples [t = 4.79; p < 0.001] but less than BPD and ADHD + BPD [p < 0.001]. As for the comparison in ED between ADHD and cyclothymia, Brancati et al [68] only found significant differences in negative emotionality and in negative/ positive emotionality ratio measured with the Reactivity, Intensity, Polarity, and Stability questionnaire (RIPoSt-40), in which adults with cyclothymia scored higher than ADHD.…”
Section: Emotion Regulation Features In Adult Adhdmentioning
confidence: 99%
“…Indeed, almost half of this subsample was diagnosed with cyclothymic disorder. Other recent studies from our group highlighted a large overlap and phenomenological similarity between patients diagnosed with adult ADHD and cyclothymic disorder [ 48 , 58 ]. Moreover, mild affective disorders, such as cyclothymia, labile personality, and minor, chronic and intermittent depressive disorders, have been diagnosed in up to 65–80% of untreated patients included in early investigations on ADHD in adults [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 82%
“…High scores on anxiety traits also were highly associated with receiving the adult ADHD label. A recent study from Italy found that about one-quarter (23.8%) of DSM-IV –defined patients with adult ADHD could be diagnosed with DSM-IV –defined cyclothymia, and a similar number of DSM-IV –defined patients with cyclothymia could be diagnosed with DSM-IV –defined adult ADHD (29.4%) (Brancati et al, 2021). All told, these studies support an overlap between bipolar illness and cyclothymia with DSM -defined adult ADHD that is in the 20% to 50% range.…”
Section: Discussionmentioning
confidence: 99%